Merton Reloaded? Book Review of Charles Crothers, Reintroducing Robert K. Merton - Audinet, Tangi (Serendipities. Journal for the Sociology and History of the Social Sciences, 2022)
Crothers, Charles (2021) Reintroducing Robert K. Merton, London; New York: Routledge 184 pp. ISBN: 9780367409678 Price: £34.99